American Labour’s Cold War Abroad: From Deep Freeze to Détente, 1945-1970 - Muldoon, Jeffrey (Relations industrielles / Industrial Relations, 2020)
The article reviews the book, "American Labour’s Cold War Abroad: From Deep Freeze to Détente, 1945-1970," by Anthony Carew.